Sire effect on early and late embryonic death in French Holstein cattle. (29th December 2014) - Ledoux, D.; Ponsart, C.; Grimard, B.; Gatien, J.; Deloche, M. C.; Fritz, S.; Lefebvre, R.; Humblot, P.
Abstract : We investigated the effect of maternal sire on early pregnancy failure (between D0, day of insemination and D90) in their progeny during the first and second lactations ( n =3508) in the Holstein breed. The estimated breeding value (EBV) for cow fertility of 12 bulls (reliability⩾0.95) was used to create the following three groups: low, medium and high EBV (EBV from −0.7 to 1 expressed as genetic standard deviation relative to the mean of the breed). In their daughters (93 to 516 per bull), progesterone measurement was carried out on the day of artificial insemination (AI; D0) to check whether the cows were in the follicular phase and on D18 to 25 to assess non-fertilisation-early embryonic mortality (NF-EEM). Late embryonic mortality (LEM) and early foetal death (FD) were determined by ultrasonography on D45 and D90 and by the return to oestrus after the first AI. Frequencies of NF-EEM, LEM, FD and pregnancy were 33.3%, 11.7%, 1.4% and 48.5% and incidences were 35.1, 19.0, 2.7 and 51.1, respectively. Sire EBV was significantly related to the incidences of pregnancy failure between D0 and D90, fertilisation failure-early embryonic mortality (FF-EEM) and LEM but not to the incidence of FD between D45 and D90 of pregnancy. The relative risk (RR) of FF-EEM was significantly higher (RR=1.2; P <0.05) for the progeny group of low EBV bulls when compared with high EBV bulls. The same effect was observed when comparing LEM of the progeny groups from the low EBV bulls to those from moderate and high EBV bulls (RR, respectively, of 1.3 and 1.4; P <005). The incidence of FF-EEM was significantly higher when cows were inseminated before 80 days postpartum compared with later, and for the extreme values of the difference between milk fat and protein content measured during the first 3 months of lactation. FF-EEM was also significantly related to the year of observation. The incidence of LEM was higher for the highest producing cows and was influenced by interaction between milk yield×lactation rank and milk yield×milk protein content. In conclusion, this study showed large differences in early pregnancy failure between progeny groups and highlights the interest of accurate characterisation of embryonic death in order to identify potential candidate genes for female fertility.